Population policy and the law - Sehgal, Brinder Pal Singh, 1951- (New Delhi : Deep & Deep Publications, 1992)
Proceedings of a seminar organized by the Dept. of Law, University of Jammu and partially sponsored by ICSSR North Western Regional Centre, Chandigarh.
PRIORITY 2.
Includes index.
Includes bibliographical references.
Keywords: Population -- Law and legislation -- India -- Congresses; India -- Population policy -- Congresses